Rare Presentation of Morganella morganii Microorganism as Epidural and Subdural Empyema - Daoud, Suleiman S.; Jarrar, Sultan; Ababneh, Obada E.; Jbarah, Omar F. (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Background Morganella morganii is a gram-negative bacterium that rarely infects the central nervous system (CNS). Few reports described such an infection in the CNS. We present a case of extremely invasive M. morganii infection in the CNS. In addition, we performed a literature review of M. morganii infection in the CNS.Case report A 53-year-old male was admitted to the hospital due to fever, general weakness, and left-sided facial muscle twitching. He had a history of diabetes mellitus, hypertension, brain tumor, and epilepsy. Multiple left frontal scalp ulcers were revealed. In addition, a computed tomography (CT) scan and magnetic resonance imaging (MRI) revealed a left side epidural abscess and subdural empyema. Moreover, the patient had left frontal bone osteomyelitis. The next day, the patient underwent craniectomy, was transferred to the intensive care unit and started an empirical antibiotic course. Morganella morganii was identified from the infected scalp ulcers. On the 13th day, the patient passed away due to uncontrolled status epilepticus.Conclusion M. morganii can cause isolated or multiple types of CNS infections, including brain abscess, meningitis, and subdural empyema. The mortality rate may differ according to age and to the use of surgical evacuation.
Keywords: subdural empyema; morganella morganii; brain infection; scalp ulcer